Kinerja Guru dalam Rangka Menghasilkan Lulusan yang Unggul Kompetitif di SDN 212 Kota Palembang - Yuliana, Yuliana; Susi Lawati; Maryanto; Amir Mahmud (Yayasan Literasi Sains Indonesia, 2025)
Teacher performance is the work results that can be achieved by someone in an educational institution or madrasah such as their duties and responsibilities in achieving educational goals. A person's success must meet the established criteria, if the teacher has met these criteria, it means that someone can be said to be successful and have good quality. The purpose of this study is to determine the performance of teachers in order to produce HR 217 graduates in the Palembang City environment. Teacher effectiveness is the teacher's teaching process which includes teaching, learning, teaching, learning, teaching, and evaluation. Teachers play an important role in ensuring professional development and encouraging student growth. They provide teaching materials, teach, and evaluate students, focusing on their skills, abilities, and motivation. Teachers also play a role in fostering student development and evaluating their progress in a continuous learning environment. This study examines the role of teachers in improving the quality of education at SDN 212 Palembang, emphasizing the importance of teacher training and development, both formal and non-formal, to improve pedagogical and professional skills, while avoiding significant impacts on student performance.